Otitis media susceptibility and shifts in the head and neck microbiome due to variants. - Frank, Daniel N; Giese, Arnaud P J; Hafrén, Lena; Bootpetch, Tori C; Yarza, Talitha Karisse L; Steritz, Matthew J; Pedro, Melquiadesa; Labra, Patrick John; Daly, Kathleen A; Tantoco, Ma Leah C; Szeremeta, Wasyl; Reyes-Quintos, Maria Rina T; et al. (J Med Genet, 2020)
BACKGROUND: Otitis media (OM) susceptibility has significant heritability; however, the role of rare variants in OM is mostly unknown. Our goal is to identify novel rare variants that confer OM susceptibility. METHODS: We performed exome and Sanger sequencing of >1000 DNA samples from 551 multiethnic families with OM and unrelated individuals, RNA-sequencing and microbiome sequencing and analyses of swabs from the outer ear, middle ear, nasopharynx and oral cavity. We also examined protein localisation and gene expression in infected and healthy middle ear tissues. RESULTS: A large, intermarried pedigree that includes 81 OM-affected and 53 unaffected individuals cosegregates two known rare variants, a common variant and a rare, novel pathogenic variant c.1682A>G (p.Glu561Gly) within (LOD=4.09). Carriage of the missense variant resulted in increased relative abundance of Microbacteriaceae in the middle ear, along with occurrence of Microbacteriaceae in the outer ear and oral cavity but not the nasopharynx. Eight additional novel variants were identified in 12 families and individuals with OM. A role for in OM susceptibility is further supported by lower RNA counts in variant carriers, strong SPINK5 localisation in outer ear skin, faint localisation to middle ear mucosa and eardrum and increased expression in human cholesteatoma. CONCLUSION: variants confer susceptibility to non-syndromic OM. These variants potentially contribute to middle ear pathology through breakdown of mucosal and epithelial barriers, immunodeficiency such as poor vaccination response, alteration of head and neck microbiota and facilitation of entry of opportunistic pathogens into the middle ear.

A2ML1 and otitis media: novel variants, differential expression, and relevant pathways. - Larson, Eric D; Magno, Jose Pedrito M; Steritz, Matthew J; Llanes, Erasmo Gonzalo D V; Cardwell, Jonathan; Pedro, Melquiadesa; Roberts, Tori Bootpetch; Einarsdottir, Elisabet; Rosanes, Rose Anne Q; Greenlee, Christopher; Santos, Rachel Ann P; Yousaf, Ayesha; et al. (Hum Mutat, 2019)
A genetic basis for otitis media is established, however, the role of rare variants in disease etiology is largely unknown. Previously a duplication variant within A2ML1 was identified as a significant risk factor for otitis media in an indigenous Filipino population and in US children. In this report exome and Sanger sequencing was performed using DNA samples from the indigenous Filipino population, Filipino cochlear implantees, US probands, Finnish, and Pakistani families with otitis media. Sixteen novel, damaging A2ML1 variants identified in otitis media patients were rare or low-frequency in population-matched controls. In the indigenous population, both gingivitis and A2ML1 variants including the known duplication variant and the novel splice variant c.4061 + 1 G>C were independently associated with otitis media. Sequencing of salivary RNA samples from indigenous Filipinos demonstrated lower A2ML1 expression according to the carriage of A2ML1 variants. Sequencing of additional salivary RNA samples from US patients with otitis media revealed differentially expressed genes that are highly correlated with A2ML1 expression levels. In particular, RND3 is upregulated in both A2ML1 variant carriers and high-A2ML1 expressors. These findings support a role for A2ML1 in keratinocyte differentiation within the middle ear as part of otitis media pathology and the potential application of ROCK inhibition in otitis media.

FUT2 Variants Confer Susceptibility to Familial Otitis Media. - Santos-Cortez, Regie Lyn P; Chiong, Charlotte M; Frank, Daniel N; Ryan, Allen F; Giese, Arnaud P J; Bootpetch Roberts, Tori; Daly, Kathleen A; Steritz, Matthew J; Szeremeta, Wasyl; Pedro, Melquiadesa; Pine, Harold; Yarza, Talitha Karisse L; et al. (Am J Hum Genet, 2018)
Non-secretor status due to homozygosity for the common FUT2 variant c.461G>A (p.Trp154) is associated with either risk for autoimmune diseases or protection against viral diarrhea and HIV. We determined the role of FUT2 in otitis media susceptibility by obtaining DNA samples from 609 multi-ethnic families and simplex case subjects with otitis media. Exome and Sanger sequencing, linkage analysis, and Fisher exact and transmission disequilibrium tests (TDT) were performed. The common FUT2 c.604C>T (p.Arg202) variant co-segregates with otitis media in a Filipino pedigree (LOD = 4.0). Additionally, a rare variant, c.412C>T (p.Arg138Cys), is associated with recurrent/chronic otitis media in European-American children (p = 1.2 × 10) and US trios (TDT p = 0.01). The c.461G>A (p.Trp154) variant was also over-transmitted in US trios (TDT p = 0.01) and was associated with shifts in middle ear microbiota composition (PERMANOVA p < 10) and increased biodiversity. When all missense and nonsense variants identified in multi-ethnic US trios with CADD > 20 were combined, FUT2 variants were over-transmitted in trios (TDT p = 0.001). Fut2 is transiently upregulated in mouse middle ear after inoculation with non-typeable Haemophilus influenzae. Four FUT2 variants-namely p.Ala104Val, p.Arg138Cys, p.Trp154, and p.Arg202-reduced A antigen in mutant-transfected COS-7 cells, while the nonsense variants also reduced FUT2 protein levels. Common and rare FUT2 variants confer susceptibility to otitis media, likely by modifying the middle ear microbiome through regulation of A antigen levels in epithelial cells. Our families demonstrate marked intra-familial genetic heterogeneity, suggesting that multiple combinations of common and rare variants plus environmental factors influence the individual otitis media phenotype as a complex trait.

Rare A2ML1 variants confer susceptibility to otitis media. - Santos-Cortez, Regie Lyn P; Chiong, Charlotte M; Reyes-Quintos, Ma Rina T; Tantoco, Ma Leah C; Wang, Xin; Acharya, Anushree; Abbe, Izoduwa; Giese, Arnaud P; Smith, Joshua D; Allen, E Kaitlynn; Li, Biao; Cutiongco-de la Paz, Eva Maria; et al. (Nat Genet, 2015)
A duplication variant within the middle ear-specific gene A2ML1 cosegregates with otitis media in an indigenous Filipino pedigree (LOD score = 7.5 at reduced penetrance) and lies within a founder haplotype that is also shared by 3 otitis-prone European-American and Hispanic-American children but is absent in non-otitis-prone children and >62,000 next-generation sequences. We identified seven additional A2ML1 variants in six otitis-prone children. Collectively, our studies support a role for A2ML1 in the pathophysiology of otitis media.
Keywords: alpha-Macroglobulins; Animals; Base Sequence; Child; Cochlea; Exome; Family Health; Female; Gene Duplication; Gene Frequency; Genetic Predisposition to Disease; Genotype; Haplotypes; Humans; Male; Mice, Inbred C57BL; Models, Molecular; Otitis Media; Pedigree; Principal Component Analysis; Protein Conformation; Sequence Analysis, DNA